A Simple, Rapid Analysis, Portable, Low-cost, and Arduino-based Spectrophotometer with White LED as a Light Source for Analyzing Solution Concentration - Asep Bayu Dani Nandiyanto; Rena Zaen; Rosi Oktiani; Ade Gafar Abdullah; Lala Septem Riza (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The purpose of this study was to demonstrate a simple, rapid analysis, portable, and inexpensive spectrophotometer. Different from other spectrophotometers, the present instrument consisted of a single white light-emmiting-diode (LED) as a light source, a light sensor, and arduino electronic card as an acquisition system. To maintain a constant light intensity, a common white-color LED emitting a 450-620 nm continous spectrum was employed. Software was written in C++ to control photometer through a USB interface and for data acquistion to the computer. The instrument is designed to be simple and compacted with sizes of 200 x 130 x 150 mm for length, width, and height, respectively. The analysis of the total cost isabout less than 500 USD, while commercially available offers price of more than 10,000 USD. Thus, this makes the present instrument feasible for teaching support media in developing countries. The effectiveness of the present spectrophotometer for analyzing solution concentration (i.e. curcumin) was also demonstrated. Interestingly, the present spectrophotometer is able to measure the concentration of curcumin precisely with an accuracy of more than 90%. Different from commercially available standard UV-visible spectrophotometers that have limitations in the analysis of concentration of less than 50 ppm, the present system can measure the concentration with no limitation since the measurement is based on the LED light being penetrated.